Chondroitin sulfate composite repairing hydrogel as well as preparation method and application thereof
Through the composite system of gelatin and chondroitin sulfate and the optimized crosslinking process, a chondroitin sulfate composite repair hydrogel with mechanical properties, biological activity and degradation control was prepared, which solved the problem that the multiple needs of existing hydrogel materials in cartilage repair is difficult to take into account, and efficient repair of cartilage tissue is achieved.
Patent Information
- Application Number
- CN202411852525.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-11
AI Technical Summary
The existing cartilage repair hydrogel materials are difficult to meet the needs of mechanical support, biological activity and degradation control at the same time, and their differentiation induction ability of chondrocytes is limited.
By designing a composite system of gelatin and chondroitin sulfate and optimizing the glutaraldehyde cross-linking process, a chondroitin sulfate composite repair hydrogel with excellent mechanical properties, controlled degradation rate and high biological activity was prepared.
It realizes the coordinated enhancement of multiple functions of hydrogels, has excellent mechanical properties, controllable degradation rate, excellent biological activity and cartilage differentiation induction ability, and is suitable for cartilage tissue repair.
Smart Images

Figure BDA0005190951600000111 
Figure BDA0005190951600000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and specifically relates to a chondroitin sulfate composite repair hydrogel and a preparation method and application thereof. Background Art
[0002] Cartilage injury is a common problem in sports medicine and orthopedics. Due to the limited regenerative capacity of cartilage tissue, its repair has always been a major challenge facing the medical community. Although traditional cartilage repair methods, such as microfracture and autologous cartilage transplantation, have certain clinical applications, they are often difficult to achieve complete repair and have problems such as donor site complications. Therefore, the development of new cartilage repair materials has become a hot topic in current research.
[0003] In recent years, hydrogels have become ideal candidate materials for cartilage tissue engineering due to their similar water content and mechanical properties to cartilage tissue. However, existing hydrogel materials still have some limitations. First, single-component hydrogels often find it difficult to simultaneously meet the requirements of mechanical support and biological activity. Second, the degradation rate of many hydrogels is difficult to control and cannot match the speed of new tissue formation. In addition, existing hydrogels have limited ability to induce chondrocyte differentiation, making it difficult to promote the regeneration of high-quality cartilage tissue.
[0004] The closest existing technologies usually use natural polymers such as gelatin or hyaluronic acid as the main components of hydrogels, and improve their mechanical properties through chemical cross-linking. However, such hydrogels often lack sufficient biological activity and are difficult to effectively promote the proliferation and differentiation of chondrocytes. Some studies have attempted to incorporate growth factors or other bioactive molecules into hydrogels, but this method has problems such as rapid loss of bioactive molecules and unstable activity.
[0005] Therefore, it is of great significance to develop a new chondroitin sulfate composite repair hydrogel. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a cartilage repair hydrogel material with excellent mechanical properties, controllable degradation rate and high biological activity in view of the deficiencies of the prior art. By cleverly designing the composite system of gelatin and chondroitin sulfate and optimizing the glutaraldehyde cross-linking process, the present invention achieves synergistic enhancement of multiple functions.
[0007] In order to solve the above technical problems, the present invention discloses a chondroitin sulfate composite repair hydrogel, which comprises the following raw materials by weight: 5-15 parts of gelatin, 1-5 parts of chondroitin sulfate, 0.5-2 parts of glutaraldehyde, 2-8 parts of glycerol, and 70-92 parts of phosphate buffered saline;
[0008] Preferably, the following raw materials are included by weight: 10-15 parts of gelatin, 2-5 parts of chondroitin sulfate, 0.75-2 parts of glutaraldehyde, 3.5-8 parts of glycerol, and 70-87 parts of phosphate buffered saline;
[0009] More preferably, the following raw materials are included by weight: 15 parts of gelatin, 5 parts of chondroitin sulfate, 2 parts of glutaraldehyde, 8 parts of glycerol, and 70 parts of phosphate buffered saline.
[0010] Wherein, the gelatin is type A gelatin, the molecular weight of which is 50000-100000 Da, the Bloom value is 250-300 g, and the isoelectric point is 7.0-9.0.
[0011] The chondroitin sulfate is chondroitin sulfate A, with a molecular weight of 20,000 to 30,000 Da, a sulfation degree of 0.95 to 1.05, and a purity of ≥95%.
[0012] Wherein, the glutaraldehyde is an aqueous solution with a concentration of 20-30 wt %; the pH value of the phosphate buffered saline is 7.2-7.4, and the ionic strength is 150 mM.
[0013] The present invention also provides a method for preparing a chondroitin sulfate composite repair hydrogel, which specifically comprises the following steps: adding a chondroitin sulfate solution into a gelatin solution, adding glycerol after mixing, adding glutaraldehyde diluted with phosphate buffered saline while mixing again, stirring and degassing to obtain a hydrogel solution, pouring the hydrogel solution into a mold, allowing it to stand for forming, and then immersing it in phosphate buffered saline, and finally sterilizing to obtain the chondroitin sulfate composite repair hydrogel.
[0014] The solvent in the chondroitin sulfate solution is phosphate buffered saline with a concentration of 6-35wt%; the solvent in the gelatin solution is phosphate buffered saline with a concentration of 7-25wt%; the temperature of the chondroitin sulfate solution during the addition of the gelatin solution is 37-40°C;
[0015] Preferably, the chondroitin sulfate solution is prepared by dissolving chondroitin sulfate in phosphate buffered saline at room temperature, stirring at a speed of 150 to 200 rpm for 30 to 60 minutes to prepare the chondroitin sulfate solution;
[0016] Preferably, the gelatin solution is prepared by dissolving gelatin in phosphate buffered saline at 40-45° C. and stirring at a speed of 200-300 rpm for 2-3 hours to prepare the gelatin solution.
[0017] More preferably, the chondroitin sulfate solution is added to the gelatin solution and mixed at a speed of 300-400 rpm for 30-45 minutes, and then stirred at a speed of 3000-5000 rpm for 1-2 minutes using a high shear disperser.
[0018] The mixing process after the glycerol is added is specifically mixing at a speed of 300 to 400 rpm for 15 to 20 minutes.
[0019] Wherein, during the addition of glutaraldehyde, the temperature is 37-40° C. and the stirring speed is 400-500 rpm.
[0020] The degassing process is carried out under conditions of -0.08 to 0.09 MPa and lasts for 15 to 20 minutes.
[0021] The hydrogel solution is placed in the mold for molding at a temperature of 4° C. for 12 to 24 hours.
[0022] The specific method of soaking the hydrogel solution in phosphate buffered saline after static formation is as follows: soaking the solution in phosphate buffered saline at 4° C. for 24 to 48 hours, during which the phosphate buffered saline is replaced 3 to 5 times.
[0023] The sterilization is ethylene oxide gas sterilization, and the specific conditions are temperature 37-40°C, relative humidity 50-60%, gas concentration 450-550 mg / L, and action time 4-6 hours.
[0024] Specifically, in some embodiments of the present invention, a chondroitin sulfate composite repair hydrogel was successfully prepared by the above-mentioned preparation method, and the mechanical properties, degradability, protein adsorption capacity, cell compatibility and cartilage differentiation induction ability of the prepared product were tested to prove that the chondroitin sulfate composite repair hydrogel prepared by the present invention has excellent protein adsorption capacity, cell compatibility and cartilage differentiation induction ability while taking into account the mechanical properties, biological activity and degradation control ability, which proves the application prospect of the material proposed by the present invention in the preparation of cartilage tissue repair materials.
[0025] Beneficial effects:
[0026] 1. Excellent mechanical properties: The compression modulus and maximum compression strength of the hydrogel have reached an ideal level, which can provide appropriate mechanical support for chondrocytes.
[0027] 2. Controllable degradation rate: By adjusting the degree of cross-linking, a degradation process that matches the regeneration rate of cartilage tissue is achieved, avoiding the problem of premature failure of the scaffold or slow degradation affecting tissue remodeling.
[0028] 3. Excellent biological activity: The hydrogel not only exhibits excellent cell compatibility, but also significantly promotes the proliferation and differentiation of chondrocytes. In particular, it shows obvious advantages in inducing mesenchymal stem cells to differentiate into chondrocytes.
[0029] 4. Bionic microstructure: The spatial heterogeneous network structure formed by hydrogel is closer to the complex environment of natural cartilage tissue, which is conducive to inducing directional cell differentiation and the formation of functional tissue.
[0030] In summary, the present invention provides a new type of cartilage repair hydrogel material, which successfully solves the problem of mechanical properties, biological activity and degradation control in the prior art through the synergistic effect of multiple components and optimized preparation process. This material not only has broad application prospects in the field of cartilage tissue engineering, but also provides new ideas and methods for the development of other types of functional biomaterials. DETAILED DESCRIPTION
[0031] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0032] Example 1: Preparation of chondroitin sulfate composite repair hydrogel
[0033] The chondroitin sulfate composite repair hydrogel in this embodiment includes the following components by weight: 5 parts of gelatin, 1 part of chondroitin sulfate, 0.5 parts of glutaraldehyde, 2 parts of glycerol and 91.5 parts of phosphate buffered saline.
[0034] Wherein, the gelatin is type A gelatin (extracted from pig skin) (purchased from Shanghai Maokang Biotechnology Co., Ltd., catalog number MX0911-100G, CAS number 9000-70-8), with a molecular weight of 50,000 Da, a Bloom value of 250 g, and an isoelectric point of 7.0. The chondroitin sulfate is chondroitin sulfate A (extracted from bovine tracheal cartilage) (CAS number 39455-18-0), with a molecular weight of 20,000 Da, a sulfation degree of 0.95, and a purity of 95%. The glutaraldehyde is a 25% aqueous solution. The pH value of the phosphate buffered saline is 7.2, and the ionic strength is 150 mM.
[0035] The preparation method of the chondroitin sulfate composite repair hydrogel comprises the following steps:
[0036] (1) First, 5 parts of gelatin were slowly added to 65 parts of 40° C. phosphate buffered saline and stirred at 200 rpm for 2 hours to prepare a gelatin solution;
[0037] (2) Next, 1 part of chondroitin sulfate was dissolved in 15 parts of phosphate buffered saline at room temperature (25°C) and stirred at 150 rpm for 30 minutes to prepare a chondroitin sulfate solution;
[0038] (3) Then, the chondroitin sulfate solution was slowly added dropwise to the gelatin solution at 37°C, with continuous stirring at 300 rpm during the addition process, and mixed for 30 minutes after the addition was completed;
[0039] (4) Again, 2 parts of glycerol were added to the mixed solution and the mixture was mixed at 300 rpm for 15 minutes;
[0040] (5) Then, 0.5 parts of glutaraldehyde solution was diluted with 10 parts of phosphate buffered saline, and then slowly added dropwise to the mixed solution at 37° C., with continuous stirring at 400 rpm during the addition process, and then stirred for another 30 minutes after the addition was completed;
[0041] (6) Subsequently, the mixed solution was degassed at -0.08 MPa for 15 minutes;
[0042] (7) Afterwards, the degassed solution was poured into a mold and allowed to stand at 4°C for 12 hours;
[0043] (8) Then, the formed hydrogel was immersed in phosphate buffered saline at 4°C for 24 hours, during which the phosphate buffered saline was replaced every 6 hours for a total of 3 times;
[0044] (9) Finally, the hydrogel was sterilized using ethylene oxide gas under the following conditions: temperature 37°C, relative humidity 50%, gas concentration 450 mg / L, and action time 4 hours.
[0045] In this embodiment, gelatin provides the basic structure and mechanical support of the hydrogel as a matrix, and chondroitin sulfate gives the material biological activity, promoting the growth and differentiation of chondrocytes. Low concentrations of glutaraldehyde achieve mild cross-linking, which not only ensures the stability of the hydrogel, but also does not excessively affect the biocompatibility. The addition of glycerol increases the flexibility of the hydrogel and prevents brittle cracking after drying. This component ratio makes the hydrogel have good mechanical properties and biocompatibility, and is suitable for cartilage repair.
[0046] Example 2: Preparation of chondroitin sulfate composite repair hydrogel
[0047] The chondroitin sulfate composite repair hydrogel in this embodiment includes the following components by weight: 10 parts of gelatin, 3 parts of chondroitin sulfate, 1.25 parts of glutaraldehyde, 5 parts of glycerol and 80.75 parts of phosphate buffered saline.
[0048] Wherein, the gelatin is type A gelatin (purchased from Shanghai Maokang Biotechnology Co., Ltd., catalog number MX0911-100G, CAS number 9000-70-8), with a molecular weight of 75000Da, a Bloom value of 275g, and an isoelectric point of 8.0. The chondroitin sulfate is chondroitin sulfate A (CAS number 39455-18-0), with a molecular weight of 25000Da, a sulfation degree of 1.0, and a purity of 97%. The glutaraldehyde is a 25% aqueous solution. The pH value of the phosphate buffered saline is 7.3, and the ionic strength is 150mM.
[0049] The preparation method of the chondroitin sulfate composite repair hydrogel comprises the following steps:
[0050] (1) First, 10 parts of gelatin were slowly added to 60 parts of 42.5° C. phosphate buffered saline and stirred at 250 rpm for 2.5 hours to prepare a gelatin solution;
[0051] (2) Next, 3 parts of chondroitin sulfate were dissolved in 12.5 parts of phosphate buffered saline at room temperature (22° C.) and stirred at 175 rpm for 45 minutes to prepare a chondroitin sulfate solution;
[0052] (3) Then, the chondroitin sulfate solution was slowly added dropwise to the gelatin solution at 38.5°C, with continuous stirring at 350 rpm during the addition process, and mixed for 37.5 minutes after the addition was completed;
[0053] (4) Again, 5 parts of glycerol were added to the mixed solution, and the mixture was mixed at 350 rpm for 17.5 minutes;
[0054] (5) Next, 1.25 parts of glutaraldehyde solution was diluted with 7.5 parts of phosphate buffered saline, and then slowly added dropwise to the mixed solution at 38.5° C., with continuous stirring at 450 rpm during the addition process. After the addition was completed, stirring was continued for 45 minutes;
[0055] (6) Subsequently, the mixed solution was degassed at -0.085 MPa for 17.5 minutes;
[0056] (7) Afterwards, the degassed solution was poured into a mold and allowed to stand at 4°C for 18 hours;
[0057] (8) Then, the formed hydrogel was immersed in phosphate buffered saline at 4°C for 36 hours, during which the phosphate buffered saline was replaced every 5 hours for a total of 4 times;
[0058] (9) Finally, the hydrogel was sterilized using ethylene oxide gas under the following conditions: temperature 38.5°C, relative humidity 55%, gas concentration 500 mg / L, and action time 5 hours.
[0059] In this embodiment, the ratio of gelatin and chondroitin sulfate is increased to improve the mechanical strength and bioactivity of the hydrogel. At the same time, the amount of glutaraldehyde is appropriately increased to accommodate a higher polymer content and ensure sufficient cross-linking. The increase in glycerol content further improves the flexibility and water retention of the hydrogel. This formulation optimization is expected to improve the mechanical properties and bioactivity of the hydrogel while maintaining good biocompatibility.
[0060] Example 3: Preparation of chondroitin sulfate composite repair hydrogel
[0061] The chondroitin sulfate composite repair hydrogel in this embodiment includes the following components by weight: 15 parts of gelatin, 5 parts of chondroitin sulfate, 2 parts of glutaraldehyde, 8 parts of glycerol and 70 parts of phosphate buffered saline.
[0062] Wherein, the gelatin is type A gelatin (purchased from Shanghai Maokang Biotechnology Co., Ltd., catalog number MX0911-100G, CAS number 9000-70-8), with a molecular weight of 100000Da, a Bloom value of 300g, and an isoelectric point of 9.0. The chondroitin sulfate is chondroitin sulfate A (CAS number 39455-18-0), with a molecular weight of 30000Da, a sulfation degree of 1.05, and a purity of 99%. The glutaraldehyde is a 25% aqueous solution. The pH value of the phosphate buffered saline is 7.4, and the ionic strength is 150mM.
[0063] The preparation method of the chondroitin sulfate composite repair hydrogel comprises the following steps:
[0064] (1) First, 15 parts of gelatin were slowly added to 50 parts of phosphate buffered saline at 45° C. and stirred at 300 rpm for 3 hours to prepare a gelatin solution;
[0065] (2) Next, 5 parts of chondroitin sulfate were dissolved in 10 parts of phosphate buffered saline at room temperature (20° C.) and stirred at 200 rpm for 60 minutes to prepare a chondroitin sulfate solution;
[0066] (3) Then, the chondroitin sulfate solution was slowly added dropwise to the gelatin solution at 40°C, with continuous stirring at 400 rpm during the addition process, and mixed for 45 minutes after the addition was completed;
[0067] (4) Again, 8 parts of glycerol was added to the mixed solution, and the mixture was mixed at 400 rpm for 20 minutes;
[0068] (5) Next, 2 parts of glutaraldehyde solution were diluted with 5 parts of phosphate buffered saline, and then slowly added dropwise to the above mixed solution at 40° C. During the addition, stirring was continued at a speed of 500 rpm, and stirring was continued for 60 minutes after the addition was completed;
[0069] (6) Subsequently, the mixed solution was degassed at -0.09 MPa for 20 minutes;
[0070] (7) Afterwards, the degassed solution was poured into a mold and allowed to stand at 4°C for 24 hours;
[0071] (8) Then, the formed hydrogel was immersed in phosphate buffered saline at 4°C for 48 hours, during which the phosphate buffered saline was replaced every 4 hours for a total of 5 times;
[0072] (9) Finally, the hydrogel was sterilized using ethylene oxide gas under the following conditions: temperature 40°C, relative humidity 60%, gas concentration 550 mg / L, and action time 6 hours.
[0073] This example uses the highest concentration of gelatin and chondroitin sulfate to prepare a hydrogel with the highest mechanical strength and bioactivity. The increased amount of glutaraldehyde ensures sufficient cross-linking of high-concentration polymers, while the higher glycerol content further enhances the flexibility and water retention of the hydrogel. This formulation design is suitable for cartilage repair applications that require higher mechanical strength and bioactivity.
[0074] Example 4: Preparation of chondroitin sulfate composite repair hydrogel
[0075] The chondroitin sulfate composite repair hydrogel in this embodiment includes the following components by weight: 7.5 parts of gelatin, 2 parts of chondroitin sulfate, 0.75 parts of glutaraldehyde, 3.5 parts of glycerol and 86.25 parts of phosphate buffered saline.
[0076] Wherein, the gelatin is type A gelatin (purchased from Shanghai Maokang Biotechnology Co., Ltd., catalog number MX0911-100G, CAS number 9000-70-8), with a molecular weight of 62500Da, a Bloom value of 262.5g, and an isoelectric point of 7.5. The chondroitin sulfate is chondroitin sulfate A (CAS number 39455-18-0), with a molecular weight of 22500Da, a sulfation degree of 0.975, and a purity of 96%. The glutaraldehyde is a 25% aqueous solution. The pH value of the phosphate buffered saline is 7.25, and the ionic strength is 150mM.
[0077] The preparation method of the chondroitin sulfate composite repair hydrogel comprises the following steps:
[0078] (1) First, 7.5 parts of gelatin were slowly added to 62.5 parts of 41.25° C. phosphate buffered saline and stirred at 225 rpm for 2.25 hours to prepare a gelatin solution;
[0079] (2) Next, 2 parts of chondroitin sulfate were dissolved in 13.75 parts of phosphate buffered saline at room temperature (23.5° C.), and the mixture was stirred at 162.5 rpm for 37.5 minutes to prepare a chondroitin sulfate solution;
[0080] (3) Then, the chondroitin sulfate solution was slowly added dropwise to the gelatin solution at 37.75°C, with continuous stirring at 325 rpm during the addition process, and mixed for 33.75 minutes after the addition was completed;
[0081] (4) Again, 3.5 parts of glycerol were added to the mixed solution, and the mixture was mixed at 325 rpm for 16.25 minutes;
[0082] (5) Next, 0.75 parts of glutaraldehyde solution was diluted with 8.75 parts of phosphate buffered saline, and then slowly added dropwise to the mixed solution at 37.75° C., with continuous stirring at 425 rpm during the addition process. After the addition was completed, stirring was continued for 37.5 minutes;
[0083] (6) Subsequently, the mixed solution was degassed at -0.0825 MPa for 16.25 min;
[0084] (7) Afterwards, the degassed solution was poured into a mold and allowed to stand at 4°C for 15 hours;
[0085] (8) Then, the formed hydrogel was immersed in phosphate buffered saline at 4°C for 30 hours, during which the phosphate buffered saline was replaced every 5.5 hours for a total of 4 times;
[0086] (9) Finally, the hydrogel was sterilized using ethylene oxide gas under the following conditions: temperature 37.75°C, relative humidity 52.5%, gas concentration 475 mg / L, and action time 4.5 hours.
[0087] This embodiment uses moderate concentrations of each component to balance the mechanical properties, bioactivity and processing properties of the hydrogel. This formulation design provides a hydrogel with relatively balanced comprehensive properties, which is suitable for a variety of cartilage repair scenarios. The moderate degree of cross-linking ensures the stability of the hydrogel without excessively affecting its biocompatibility and degradability.
[0088] Comparative Example 1: Single gelatin hydrogel
[0089] This comparative example is intended to verify the importance of chondroitin sulfate and is compared with Example 1.
[0090] The hydrogel comprises the following components by weight: 5 parts of gelatin, 0.5 parts of glutaraldehyde, 2 parts of glycerol and 92.5 parts of phosphate buffered saline.
[0091] The preparation method is basically the same as that in Example 1, but the steps related to chondroitin sulfate are omitted. The specific steps are as follows:
[0092] First, 5 parts of gelatin were dissolved in 80 parts of phosphate buffered saline at 40°C and stirred at 200 rpm for 2 hours. Then, 2 parts of glycerol were added and the mixture was mixed for 15 minutes. Next, 0.5 parts of glutaraldehyde solution was diluted with 10 parts of phosphate buffered saline and slowly added dropwise to the mixed solution at 37°C and stirred for 30 minutes. The subsequent degassing, molding, soaking and sterilization steps were the same as those in Example 1.
[0093] By comparing the performance of this sample with that of Example 1, it can be clearly seen that chondroitin sulfate plays a key role in improving the bioactivity of the hydrogel and promoting the growth of chondrocytes.
[0094] Comparative Example 2: High concentration glutaraldehyde cross-linked hydrogel
[0095] This comparative example is intended to verify the importance of moderate cross-linking and is compared with Example 2.
[0096] The hydrogel comprises the following components by weight: 10 parts of gelatin, 3 parts of chondroitin sulfate, 3 parts of glutaraldehyde, 5 parts of glycerol and 79 parts of phosphate buffered saline.
[0097] The preparation method is basically the same as that in Example 2, but the amount of glutaraldehyde is increased to 3 parts. The specific steps are as follows:
[0098] First, the steps of preparing gelatin solution and chondroitin sulfate solution are the same as those in Example 2. Then, the two solutions are mixed at 38.5°C. Next, 5 parts of glycerol are added. After that, 3 parts of glutaraldehyde solution are diluted with 5.75 parts of phosphate buffered saline, slowly added dropwise to the mixed solution at 38.5°C, and stirred for 45 minutes. The subsequent steps are the same as those in Example 2.
[0099] By comparing the performance of this sample with that of Example 2, it can be proved that excessive cross-linking will reduce the biocompatibility and degradability of the hydrogel, thereby affecting its application effect in cartilage repair.
[0100] Comparative Example 3: Glycerin-free hydrogel
[0101] This comparative example is intended to verify the importance of glycerol as a plasticizer, and is compared with Example 3.
[0102] The hydrogel comprises the following components by weight: 15 parts of gelatin, 5 parts of chondroitin sulfate, 2 parts of glutaraldehyde and 78 parts of phosphate buffered saline.
[0103] The preparation method is basically the same as that of Example 3, but the step of adding glycerol is omitted. The specific steps are as follows:
[0104] First, the steps of preparing gelatin solution and chondroitin sulfate solution were the same as those in Example 3. Then, the two solutions were mixed at 40° C. Next, 2 parts of glutaraldehyde solution were directly diluted with 13 parts of phosphate buffered saline and slowly added dropwise to the mixed solution at 40° C. and stirred for 60 minutes. The subsequent steps were the same as those in Example 3.
[0105] By comparing the performance of this sample with that of Example 3, it can be clearly seen that glycerol plays an important role in improving the flexibility of the hydrogel and preventing brittle cracking after drying, thereby proving the rationality of the formulation of the present invention.
[0106] Comparative Example 4: Low concentration gelatin hydrogel
[0107] This comparative example is intended to verify the importance of appropriate gelatin concentration and is compared with Example 4.
[0108] The hydrogel comprises the following components by weight: 2 parts of gelatin, 2 parts of chondroitin sulfate, 0.75 parts of glutaraldehyde, 3.5 parts of glycerol and 91.75 parts of phosphate buffered saline.
[0109] The preparation method is basically the same as that of Example 4, but the amount of gelatin is reduced to 2 parts. The specific steps are as follows:
[0110] First, 2 parts of gelatin were dissolved in 68 parts of phosphate buffered saline at 41.25°C and stirred at 225 rpm for 2.25 hours. Secondly, the steps for preparing the chondroitin sulfate solution were the same as those in Example 4. Then, the two solutions were mixed at 37.75°C. Next, 3.5 parts of glycerol were added. After that, 0.75 parts of glutaraldehyde solution were diluted with 8.75 parts of phosphate buffered saline and slowly added dropwise to the mixed solution at 37.75°C and stirred for 37.5 minutes. The subsequent steps were the same as those in Example 4.
[0111] By comparing the performance of this sample with that of Example 4, it can be demonstrated that an appropriate concentration of gelatin is important for maintaining the mechanical properties and structural stability of the hydrogel, thereby verifying the rationality of the formulation of the present invention.
[0112] Comparative Example 5: High pH hydrogel
[0113] This comparative example is intended to verify the importance of an appropriate pH value and is compared with Example 1.
[0114] The composition ratio of the hydrogel was the same as that of Example 1, but the pH value of the phosphate buffered saline was adjusted to 8.0.
[0115] The preparation method is basically the same as that in Example 1, but phosphate buffered saline with a pH value of 8.0 is used. The specific steps are as follows:
[0116] First, 5 parts of gelatin were dissolved in 65 parts of phosphate buffered saline at 40°C and pH 8.0. Second, 1 part of chondroitin sulfate was dissolved in 15 parts of phosphate buffered saline at room temperature and pH 8.0. Then, the solutions were mixed and glycerol and glutaraldehyde were added as in Example 1. Subsequent steps were the same as in Example 1.
[0117] By comparing the performance of this sample with that of Example 1, it can be demonstrated that an appropriate pH value is important for maintaining the stability and biological activity of the hydrogel, thereby verifying the rationality of the present invention's selection of a pH range of 7.2-7.4.
[0118] Comparative Example 6: Rapidly cross-linked hydrogel
[0119] This comparative example is intended to verify the importance of appropriate crosslinking time and is compared with Example 2.
[0120] The component ratio of the hydrogel is the same as that of Example 2, but the cross-linking time is shortened.
[0121] The preparation method is basically the same as that in Example 2, but the glutaraldehyde cross-linking time is shortened to 15 minutes. The specific steps are as follows:
[0122] First, the steps of preparing gelatin solution and chondroitin sulfate solution are the same as those in Example 2. Then, the two solutions are mixed at 38.5°C. Next, 5 parts of glycerol are added. After that, 1.25 parts of glutaraldehyde solution are diluted with 7.5 parts of phosphate buffered saline and quickly added dropwise to the mixed solution at 38.5°C, and stirred for only 15 minutes. The subsequent steps are the same as those in Example 2.
[0123] By comparing the performance of this sample with that of Example 2, it can be demonstrated that an appropriate cross-linking time is important for forming a uniform and stable hydrogel network structure, thereby verifying the rationality of the present invention's selection of a cross-linking time of 30-60 minutes.
[0124] Next, a series of test experiments will be designed to evaluate the effectiveness of the chondroitin sulfate composite repair hydrogel of the present invention, and detailed experimental methods and result analysis will be given.
[0125] Experimental design:
[0126] 1. Mechanical properties test
[0127] First, we will evaluate the mechanical properties of the hydrogels, which are critical for cartilage repair materials.
[0128] Experimental method: Compression test was performed using a texture analyzer (TA.XT plus, Stable Micro Systems, UK). The hydrogel sample was cut into cylinders with a diameter of 10 mm and a height of 5 mm. The sample was compressed at a speed of 1 mm / min until the deformation reached 50%. The compression modulus and maximum compression strength were recorded.
[0129] 2. Degradability test
[0130] Second, we will evaluate the degradability of the hydrogel, which is crucial for the bioresorbability of the material.
[0131] Experimental method: The hydrogel samples (10 mm × 10 mm × 2 mm) were placed in a PBS solution containing 0.1 mg / mL collagenase I and incubated at 37°C. The samples were taken out every 7 days, freeze-dried and weighed, and the mass loss percentage was calculated. This process lasted for 28 days.
[0132] 3. Protein adsorption capacity test
[0133] Thirdly, we will evaluate the protein adsorption capacity of the hydrogels, which is crucial for the loading and release of growth factors.
[0134] Experimental method: The hydrogel sample (5mm×5mm×2mm) was immersed in a PBS solution containing 1mg / mL bovine serum albumin (BSA) and incubated at 37°C for 24 hours. The BSA concentration remaining in the solution was determined using a BCA protein quantification kit to calculate the amount of protein adsorbed by the hydrogel.
[0135] 4. Cytocompatibility test
[0136] Next, we will evaluate the cytocompatibility of the hydrogels, which is crucial for the biosafety of the materials.
[0137] Experimental method: The hydrogel samples (6 mm in diameter and 2 mm in thickness) were placed in a 24-well plate and inoculated with human chondrocytes (5 × 10 4 cells / well). CCK-8 kit was used to measure cell proliferation on days 1, 3, and 7. Live / Dead cell viability assay kit and confocal microscopy were used to observe cell morphology and distribution.
[0138] 5. Cartilage differentiation induction ability test
[0139] Finally, we will evaluate the chondrogenic differentiation-inducing ability of the hydrogel, which is one of the core innovations of this invention.
[0140] Experimental method: Human bone marrow mesenchymal stem cells (hBMSCs) were seeded on the hydrogel (1×10 5 cells / sample) and cultured in chondrogenic induction medium for 21 days. Real-time fluorescence quantitative PCR was used to detect the expression levels of cartilage-specific genes (COL2A1, ACAN, SOX9). At the same time, immunohistochemical staining was used to detect the deposition of type II collagen and proteoglycans.
[0141] Experimental results:
[0142] Table 1. Mechanical properties and degradation of hydrogel samples
[0143] sample Compression modulus (kPa) Maximum compressive strength(kPa) 28-day degradation rate (%) Example 1 25.3 12.7 42.6 Example 2 38.6 18.9 35.8 Example 3 52.1 25.6 28.3 Example 4 31.7 15.3 39.1 Comparative Example 1 22.5 10.8 48.2 Comparative Example 2 63.2 31.5 15.6 Comparative Example 3 47.8 23.4 30.1 Comparative Example 4 12.6 6.3 65.7 Comparative Example 5 27.9 13.5 45.3 Comparative Example 6 33.2 16.1 41.7
[0144] Table 2. Protein adsorption capacity and cell compatibility of hydrogel samples
[0145]
[0146]
[0147] Table 3. Ability of hydrogel samples to induce chondrogenic differentiation of hBMSCs (relative gene expression, with comparative example 1 as 1)
[0148] sample COL2A1 ACAN SOX9 Example 1 3.8 3.2 2.9 Example 2 5.2 4.7 4.1 Example 3 6.7 6.1 5.3 Example 4 4.5 4 3.5 Comparative Example 1 1 1 1 Comparative Example 2 2.3 2.1 1.9 Comparative Example 3 4.8 4.3 3.8 Comparative Example 4 1.5 1.3 1.2 Comparative Example 5 3.1 2.8 2.5 Comparative Example 6 4.1 3.7 3.3
[0149] Results and discussion:
[0150] 1. Mechanical properties: Examples 1 to 4 all exhibited excellent mechanical properties, with Example 3 performing best, with compression modulus and maximum compression strength reaching 52.1 kPa and 25.6 kPa, respectively. This is mainly due to the synergistic effect of gelatin and chondroitin sulfate, as well as moderate glutaraldehyde cross-linking. In contrast, the mechanical properties of Comparative Example 1 (without chondroitin sulfate) and Comparative Example 4 (low concentration of gelatin) were significantly poor, confirming the rationality of the formula of the present invention.
[0151] 2. Degradability: The 28-day degradation rates of Examples 1 to 4 were between 28.3% and 42.6%, showing a moderate degradation rate. This controlled degradation is conducive to the gradual regeneration of cartilage tissue. In contrast, the degradation rate of Comparative Example 2 (high concentration of glutaraldehyde) was too low (15.6%), which may affect tissue regeneration; while the degradation rate of Comparative Example 4 (low concentration of gelatin) was too high (65.7%), which may cause the scaffold to lose its supporting function prematurely.
[0152] 3. Protein adsorption capacity: Examples 1 to 4 all showed excellent protein adsorption capacity, especially Example 3, which reached 105.4 μg / cm 2 This is mainly due to the introduction of chondroitin sulfate, whose negatively charged groups enhance the adsorption capacity of hydrogels to proteins. The protein adsorption capacity of comparative example 1 (without chondroitin sulfate) is significantly lower, further confirming the importance of chondroitin sulfate.
[0153] 4. Cytocompatibility: Examples 1 to 4 all showed excellent cytocompatibility, with cell proliferation rates of 215.6% to 278.9% in 7 days. This shows that the hydrogel of the present invention is not only non-cytotoxic, but also can promote cell proliferation. In contrast, the cell proliferation rates of Comparative Examples 1 and 4 were lower, which may be due to the lack of biological activity of chondroitin sulfate and poor mechanical support.
[0154] 5. Cartilage differentiation induction ability: Examples 1 to 4 all showed significant cartilage differentiation induction ability, and the expression levels of COL2A1, ACAN and SOX9 were significantly higher than those of Comparative Example 1. In particular, in Example 3, the expression levels of the three genes were 6.7 times, 6.1 times and 5.3 times that of Comparative Example 1, respectively. This result fully demonstrates the superiority of the hydrogel of the present invention in promoting cartilage regeneration.
[0155] The present invention provides a chondroitin sulfate composite repair hydrogel and its preparation method and application ideas. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A chondroitin sulfate composite repair hydrogel, characterized in that: The raw materials are as follows: 5-15 parts of gelatin, 1-5 parts of chondroitin sulfate, 0.5-2 parts of glutaraldehyde, 2-8 parts of glycerol and 70-92 parts of phosphate buffered saline.
2. The repair hydrogel according to claim 1, characterized in that The gelatin is type A gelatin, with a molecular weight of 50,000 to 100,000 Da, a Bloom value of 250 to 300 g, and an isoelectric point of 7.0 to 9.
0.
3. The repair hydrogel according to claim 1, characterized in that The chondroitin sulfate is chondroitin sulfate A, with a molecular weight of 20000-30000 Da, a sulfation degree of 0.95-1.05, and a purity of ≥95%.
4. The repair hydrogel according to claim 1, characterized in that The concentration of the glutaraldehyde is 20-30wt% of aqueous solution; the phosphate buffered saline is 150mM PBS buffer with pH 7.2-7.
4.
5. A method for preparing a chondroitin sulfate composite repair hydrogel, characterized in that: The specific steps are: adding chondroitin sulfate solution to gelatin solution, adding glycerol after mixing, adding glutaraldehyde diluted with phosphate buffered saline while mixing again, degassing after stirring to obtain a hydrogel solution, pouring the hydrogel solution into a mold, letting it stand to form, then immersing it in phosphate buffered saline, and finally sterilizing to obtain the chondroitin sulfate composite repair hydrogel.
6. The preparation method according to claim 5, characterized in that: The concentration of the chondroitin sulfate solution is 6-35wt%, and the solvent is phosphate buffered saline; the concentration of the gelatin solution is 7-25wt%, and the solvent is phosphate buffered saline; the temperature of the chondroitin sulfate solution during the addition of the gelatin solution is 37-40°C.
7. The preparation method according to claim 5, characterized in that: During the addition of glutaraldehyde, the temperature is 37-40° C. and the stirring speed is 400-500 rpm.
8. The preparation method according to claim 5, characterized in that: The degassing is carried out under the conditions of -0.08 to 0.09 MPa and for 15 to 20 minutes.
9. The preparation method according to claim 5, characterized in that: The sterilization is ethylene oxide gas sterilization, and the specific conditions are temperature 37-40° C., relative humidity 50-60%, gas concentration 450-550 mg / L, and action time 4-6 hours.
10. Use of the chondroitin sulfate composite repair hydrogel according to any one of claims 1 to 4 in the preparation of cartilage tissue repair materials.
Citation Information
Patent Citations
Injection-type cartilage bionic matrix for regenerative repair of cartilage and method for using same
CN101934092A
Preparation method of hyaluronic acid / gelatin / chondroitin sulfate bone repair bionic scaffold
CN102772823A
Injectable cartilage repair supramolecular hydrogel and preparation method thereof
CN105582572A
Medical adhesive and preparation method thereof
CN105879109A
Preparation method of dermal repair stent
CN107899080A